Values of the Land: Kinships as Climate Solutions in ‘The Honorable Harvest’ and ‘Land as Pedagogy.’ - Abigail Morton-Wilcox (New Area Studies)
Potawatomi scholar Kyle Powys Whyte’s concept of kinship time promotes responses to the climate crisis grounded in kinships and responsibilities. This article explores the land-based relationships and kinships within the essays ‘The Honorable Harvest’ by Potawatomi scholar Robin Wall Kimmerer and the essay ‘Land as Pedagogy’ by Michi Saagiig Nishnaabeg scholar Leanne Betasamosake Simpson in the context of Whyte’s kinship time theory. I centre my analysis of these essays around four values: care, consent, respect, and reciprocity. These values underpin the kinships with the natural world presented by Kimmerer and Simpson and relate to the responsibilities which Whyte identifies as foundational to kinship time. I argue that reading these texts alongside one another reveals the ways in which the kinships with the land presented by Kimmerer and Simpson are integral solutions to the climate crisis. Fundamentally, Kimmerer and Simpson reject and oppose the oppressive and exploitative systems at the centre of the climate emergency: settler colonialism and extractive capitalism, whilst simultaneously providing kinships with the living world as ways of mitigating such crises.